2006
DOI: 10.2141/jpsa.43.378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Garlic Meal on Histological Structure of Small Intestine in Broiler Chickens

Abstract: This study was conducted to evaluate the e#ect of garlic (Allium sativum) meal on the intestinal mucosal morphology of broiler chickens between ,+ and ., days of age. A total of +2**, ,+ days old Ross-*2 broiler chicks were weighed and randomly allotted into *, *.+,/, *.,/, *./, + and ,ῌ dietary garlic meal groups of each +** birds. Experimental diets were formulated by addition of each level of garlic meal to commercial finisher mash diet (CP : ,*../ῌ, ME :-,+-* kcal/kg), and fed ad libitum for ,+ d. At day .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
70
2
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 19 publications
10
70
2
8
Order By: Relevance
“…Accordingly, the villus height: crypt depth ratio was significantly higher in the birds fed the PFA compared to the control. These findings were consistent to Adibmoradi et al (2006) who reported that jejunal villus height was increased whereas crypt depths were decreased, leading to increased villus height: crypt depth ratio in birds fed graded levels of garlic meal. It has been suggested that longer villi would result in an increased surface area and higher absorption of available nutrients (Caspary, 1992;Yasar and Forbes, 1999).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, the villus height: crypt depth ratio was significantly higher in the birds fed the PFA compared to the control. These findings were consistent to Adibmoradi et al (2006) who reported that jejunal villus height was increased whereas crypt depths were decreased, leading to increased villus height: crypt depth ratio in birds fed graded levels of garlic meal. It has been suggested that longer villi would result in an increased surface area and higher absorption of available nutrients (Caspary, 1992;Yasar and Forbes, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the intestinal morphology, heavier chickens are generally associated with longer villi, greater villus width and higher villus surface area as compared to lighter ones (Adibmoradi et al, 2006;Incharoen et al, 2010). In the present study there were insignificantly increased villus heights and decreased crypt depths in the jejunum of birds receiving 150 mg/kg PFA compared to the control.…”
Section: Discussioncontrasting
confidence: 56%
“…Presumably, the reduced mortality and similar body weight gain in the garlicsupplemented group (21 d of age) in comparison with the coccidiostat-supplemented one may be the result of garlic's ability to stimulate regeneration and improvement in the physiological condition of the intestinal epithelial layer. In the study of Adibmoradi et al (2006) the addition of garlic meal (0.5%, 1%, 2% of diet) enhanced villus height and crypt depth and decreased epithelial thickness and goblet cell numbers in the duodenum, jejunum and ileum of birds. Moreover, garlic administration resulted in an increased the villus:crypt ratio in the duodenum, which is an indicator of the digestive capacity and its increase corresponds to an increase in digestion and absorption of nutrients (Adibmoradi et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…There is a strong relationship between intestinal mucosal histology and body weight change induced by intestinal function (Awad et al, 2006). Increases in villus length (Adibmoradi et al, 2006), villus width (Johnson and Jee, 1986), villus surface (Awad et al, 2006) and cell mitosis (Yamauchi et al, 2006) provide a greater surface area for higher nutrient absorptive potential and thus improve nutrient digestibility (Onderci et al, 2006). Conversely, short and narrow villi are associated with a decrease in body weight (Batal and Persons, 2002) and a reduction in the specific activity of the brush-border enzymes such as lactase and sucrase (Pluske et al, 1996) and mucosal enzymes such as peptidase and aminopeptidase (Hedmann et al, 2006).…”
Section: Discussionmentioning
confidence: 99%